Perilaku Hidup Bersih dan Sehat pada Anak-Anak di Dusun Cot Sibati Desa Blang Krueng - Nurhayati; Ridha Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aims to categorise the clean and healthy lifestyles applied in Cot Sibati, Blang Krueng Village. The research subjects were ten 7 and 8 years-old children. The data collection method was descriptive qualitative, i.e. interview, observation and documentation. Given that only three out of eight indicators met the requirements, the results indicated that both clean and healthy living habit level was fairly poor. It could be concluded that these lifestyles have not been performed by the observed subjects that may be associated with the lack of information providing the importance of cleanliness and healthiness. Keywords: clean life behavior; healthy life behavior; clean life indicators; and healthy life indicators.